Household food insecurity, dietary diversity with undernutrition among children younger than five years in Indian subcontinent-a narrative review - Surabhi Singh Yadav; Hema Matela; Pooja Panchal; Kavitha Menon (Elsevier, 2024)
Summary: The emerging predictors of childhood undernutrition include household food insecurity (HFI) and inadequate diet diversity (DD). Geographical, socio-cultural, economic, and demographic factors contribute to HFI. Earlier, HFI was often considered an outcome of hunger and poverty leading to undernutrition. The increasing availability of data related to childhood DD and its direct association with undernutrition indicates that DD could mediate the relationship between HFI and undernutrition. This narrative review examined the association of HFI and/or DD with undernutrition in children younger than 5 years in the Indian subcontinent; and the current programmes and policies. The current evidence showed a possible association between HFI and DD either independently or together with childhood undernutrition. Until now, nutrition-specific interventions to address moderate and severe forms of undernutrition were focused, with a limited attention on nutrition-sensitive approaches to improve HFI and DD. Interventions which improve HFI and DD may be included in the existing programmes and would help address the undernutrition in children younger than 5 years.